The Effect of Neal’s model on the Deep Understanding Of The Students Of The Third Intermediate Grade in Chemistry - Ahmed Laibi Hussein Al-Tamimi; Israa Naji Kadom (Eximia, 2024)
The research aimed to find out the impact of Neel’s model on the deep understanding of the third intermediate grade students in chemistry, and n Experimental design with partial control (comprised of an experimental group and a control group) was chosen. Thirty-three (33) of them were pupils from the same grade at Al-Riyadh High School for Baghdad Al-Karkh General Directorate of Education / 3 for the collegiate year (2022-2023 AD) The study sample was rewarded with the following: (intelligence, chronological age in months, previous knowledge, and deep understanding), and the researcher relied on the deep understanding test tool, and its validity and stability we discovered, and the scientific material was chosen and prepared in the form of plans (for both groups) for The research sample was used, and it was statistically analyzed using the software program Statistics. The data were then interpreted by the researcher, who then presented many directives and some ideas.